Crime scenes : Interbelluminterieurs door de lens van de forensische fotografie - Sterckx, Marjan; Vandenhove (Ghent, Belgium) ([Gent] : A & S/Books, 2021)
Photographs of crime scenes are an as yet unexplored but valuable source for research into historic interiors. They offer an uncensored glimpse into the vernacular living circumstances of various segments of the population. This book presents a selection of original photographs and maps of crime scenes in the provinces of East Flanders and Antwerp in the 1920s and '30s. Six articles deal with the potential of crime scene photography for interior research, the establishment and functioning of the judicial laboratories of Ghent and Antwerp, inter-war interiors in Flanders through the lens of forensic photographs and files, as well as two case studies, on a lodging house in Antwerp South and a cottage villa in Merksem. Exhibition: Vandenhove. Centrum voor Architectuur en Kunst, Ghent, Belgium (20.05.2021 - 10.07.2021).
Catalog of an exhibition held at Vandenhove, Gent, May 20-July 10, 2021.
boek